2018
DOI: 10.1016/j.enconman.2017.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Technical and economic optimization of subcritical, wet expansion and transcritical Organic Rankine Cycle (ORC) systems coupled with a biogas power plant

Abstract: A B S T R A C TGenerally, > 40% of the useful energy (cooling engine and exhaust gases) are wasted by a biogas power plant through the cooling radiator and the exhaust gases. An efficient way to convert this waste heat into work and eventually electricity is the use of an organic Rankine cycle (ORC) power system. Over the last few years, different architectures have been widely investigated (subcritical, wet expansion and trans-critical). Despite the promising performances, realistic economic and technical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Organic Rankine cycles (ORCs) are another opportunity to improve the efficiency of the cogeneration system by increasing the electric power output. Many authors in the literature have analyzed the feasibility of adopting an ORC in a biogas plant, and have mainly focused on the optimization of the cycle parameters such as expander geometry [16], type of architecture [16], and cycle parameters [17]. In a previous work, the authors showed that simple modifications to the digestion plant can lead to efficiency improvements over one year of operation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Organic Rankine cycles (ORCs) are another opportunity to improve the efficiency of the cogeneration system by increasing the electric power output. Many authors in the literature have analyzed the feasibility of adopting an ORC in a biogas plant, and have mainly focused on the optimization of the cycle parameters such as expander geometry [16], type of architecture [16], and cycle parameters [17]. In a previous work, the authors showed that simple modifications to the digestion plant can lead to efficiency improvements over one year of operation [18].…”
Section: Introductionmentioning
confidence: 99%
“…In other respects, as a result of the calculations made for simple ORC in the previous paper, the net power production, thermal and exergetic efficiencies are calculated as 79.23 kW, 15.51% and 27.20% for the subcritical ORC and 81.52 kW, 15.93% and 27.76% for the Different types of ORC configurations (simple, regenerative, subcritical or supercritical) has many advantageous and disadvantageous to each other. For instance, the investment cost of a supercritical ORC is higher than that of a subcritical one [12,68] Moreover, compared with the subcritical ORC, the supercritical ORC has a higher turbine inlet pressure which affects the safety as well as investment cost [69,70]. When the ORC systems are compared in term of the regenerative and simple (non-regenerative) cycle, there are many studies which prove the superiority of the performance of rORC over simple ORC [71][72][73][74][75][76].…”
Section: Effect Of the Regeneratormentioning
confidence: 99%
“…Consequently, nuclear energy and renewable energy sources such as solar [5], wind [6,7], geothermal [8] and biomass [9], which are sustainable and environmentally friendly, draw the attention of most governments, technology companies and scientists. Biogas, one of the anaerobic digestion products, is also among the most attractive alternative energy sources [10][11][12][13]. There are various biogas utilisation systems like stoves, fuel cells, gas turbines and hydrogen production systems [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ORC has at least two advantages, namely as a power generation system, ORC has simple components and the availability of components that are quite a lot in the market. Furthermore, ORC also uses organic working fluids that perform better than water as a working fluid at low temperature and pressure [12][13][14][15][16][17][18]. Various ORC applications have been reported in previous studies.…”
Section: Introductionmentioning
confidence: 99%